Real-time evaluation of the dynamic Young’s modulus for composite formations based on the drilling parameters using different machine learning algorithms - Mahmoud, Ahmed Abdulhamid; Gamal, Hany; Elkatatny, Salaheldin; Chen, Weiqing (Frontiers in Earth Science, 2022)
The dynamic Young’s Modulus (Edyn) is a parameter needed for optimizing different aspects related to the oil well designing. Currently, Edyn is determined from the knowledge of the formation bulk density, in addition to the shear and compressional velocities, which are not always available. This study introduces three machine learning (ML) models of the random forest (RF), fuzzy logic (ANFIS), and support vector regression (SVR) for estimation of the Edyn from only the real-time available drilling parameters. The ML models were learned on 2054 datasets collected from Well-A, and then tested and validated on 871 and 2912 datasets from Well-B and Well-C, respectively. The results of this study showed that the three optimized ML models accurately predicted the Edyn in the three oil wells considered in this study. The optimized SVR model outperformed both the RF and ANFIS models in evaluating the Edyn in all three wells. For the validation data, the Edyn was assessed accurately with low average absolute percentage errors of 3.64%, 6.74%, and 1.03% using the optimized RF, ANFIS, and SVR models, respectively.